2017
DOI: 10.2308/jeta-51700
|View full text |Cite
|
Sign up to set email alerts
|

Using Socrative to Enhance Instruction in an Accounting Classroom

Abstract: Are you interested in increasing the level of student engagement in your accounting course? You are not alone. In today's classroom, increased student engagement and active learning are desired by faculty and students alike. In this paper, we outline how to use Socrative Student Response by Mastery Connect (Socrative 2016), a variation of a real-time response tool called a “clicker.” We used this tool in both undergraduate and graduate-level managerial accounting courses. We provide a user's guide to Socrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…According to Kokina and Juras [22] the use of Socrative has received positive feedback from instructors and students of Energy Business and Economic Development to teaching Accounting. Although, "students react positively to the use of Socrative, the main challenge for the instructor is to make sure that the software enhances the learning process and does not become a distractor."…”
Section: Game-based Learning Toolsmentioning
confidence: 99%
“…According to Kokina and Juras [22] the use of Socrative has received positive feedback from instructors and students of Energy Business and Economic Development to teaching Accounting. Although, "students react positively to the use of Socrative, the main challenge for the instructor is to make sure that the software enhances the learning process and does not become a distractor."…”
Section: Game-based Learning Toolsmentioning
confidence: 99%
“…quizzing) stimulates students to monitor their learning and control or regulate their learning process. Quizzing can be implemented in classrooms in a high-tech setting, where students are allowed to enter their answers into some kind of device, for example clicker devices (Blasco-Arcas et al, 2013;Mayer et al, 2009), the web-based system Socrative (Balta & Tzafilkou, 2019;Kokina & Juras, 2017) or Kahoot! (Wang, 2015).…”
Section: Conceptual Framework and Literaturementioning
confidence: 99%
“…Other research on SRS in the area of accounting education can also be identified (Beekes, 2006;Cummings & Hsu, 2007;Cunningham, 2008;Kokina, J., & Juras, 2017;Marshall & Varnon, 2012;Newmark et al, 2011;Paz, 2017;Segovia, 2008;Yuen, 2018). Brazilian literature on SRS is still in its early stages.…”
Section: Prior Srs Studies In Accounting Educationmentioning
confidence: 99%